A comparison of postoperative morphometric and hemodynamic changes between saphenous vein and left internal mammary artery grafts. Issue 21 (9th November 2017) - Fan, Tingting; Feng, Yundi; Feng, Feng; Yin, Zhongjie; Luo, Dayou; Lu, Yuan; Xu, Yingjin; Tan, Wenchang; Huo, Yunlong
Abstract: There is higher long‐term failure of the saphenous vein graft (SVG) compared with the left internal mammary artery (LIMA) graft, which is affected by the hemodynamic environment. A comprehensive analysis of postoperative structure‐function changes is important to study the atherogenesis in the SVG. A comparison of morphometric and hemodynamic parameters was carried out between LIMA grafts and SVGs and between different time points postoperatively. Various parameters were obtained from the image reconstruction and flow simulation in patients, who underwent CT exams for 1 year, 5 and 10 years after revascularization. Morphometric data showed a decrease in lumen size in the entire SVG and anastomosis of different patients in a sequence of 1 year, 5 and 10 years postoperatively despite negligible changes of LIMA size. Computational results indicated the fourfold increased surface area ratio (SAR) of low time‐averaged wall shear stress (TAWSS) in the SVG and anastomosis at postoperative 10 years than that at postoperative 1 year. The SAR of high TAWSS gradient (TAWSSG) at the distal anastomosis between SVG and coronary arteries was significantly higher (14 ± 9% vs. 6 ± 8%) than that in the LIMA group at postoperative 1 year. There were strong correlations between morphometric and hemodynamic parameters in the SVG and distal anastomosis at various time points postoperatively, which showed deterioration relevant to persistent diffuse diseases at postoperative 10 years. Abstract : The retrospective study showed morphometric and hemodynamic changes in SVGs and LIMA grafts of 132 patients for 1 year, 5 and 10 years after revascularization. The findings showed that the vicious cycle of increased SAR‐TAWSS and decreased lumen size with time is a major risk factor for long‐term SVG occlusion albeit SVG arterialization and high SAR‐TAWSSG contribute to the vascular remodeling in the anastomosis within the initial years after grafting.